Optimum Condition for Polyhydroxyalkanoate Production from Crude Glycerol by Bacillus sp. Isolated from Lipid-Containing Wastewater - Pinyaphong, Porntippa; Sriburi, Pensiri (Trends in Sciences, 2022)
Polyhydroxyalkanoates (PHAs) are a group of biopolymers used as an alternative to petroleum-based synthetic plastics. Their industrial application is not widely available due to production cost constraints, mainly from raw materials used for carbon sources. This research focuses on selecting a Bacillus strain from lipid-containing wastewater that can produce PHAs from crude glycerol and investigating the optimum conditions for producing PHAs from crude glycerol. The Bacillus strain was isolated from the wastewater storage pond at a fermented pork sausage manufacturing plant in Thailand for PHAs production utilizing Mineral Salt Medium (MSM) with 1 % w/v glucose as a carbon source. PHAs synthesis was preliminarily investigated by staining cells with Sudan Black B. The isolated FMI3 produced the highest PHAs at 43 % of the dry cell weight (DCW). It was identified as Bacillus pumilus FMI3. Crude glycerol was obtained from a by-product of the transesterification of waste cooking oil catalysed by NaOH. It was partially purified by acidification and neutralization and exhibited about 80 % w/w glycerol, 1.90 ± 0.09 % ash content, 2.80 ± 0.14 % water content, light brown colour, and pH 7.11 ± 0.35. Isolated B. pumilus FMI3 grows best and produces the highest PHAs yields under optimum conditions, i.e., MSM containing crude glycerol and ammonium sulphate at 61:1 mole ratio as carbon and nitrogen sources respectively, 15 % inoculum, initial pH of neutral at 7, and shaking at 150 rpm at 40 °C for 72 h. These conditions achieved PHAs at 79 % of DCW, classified as medium-chain-length PHAs comprising 3-hydroxyoctanoate, 3-hydroxydecanoate, 3-hydroxydodecanoate, and 3-hydroxytetradecanoate at 9, 12, 67 and 12 %, respectively. This study reported the feasibility of utilizing crude glycerol as feedstock for PHAs production by the B. pumilus FMI3 strain, which was able to grow on and tolerate salts of crude glycerol. HIGHLIGHTS Bacteria which endure extreme environments (i.e., very limited of nutrients; drought and chemicals) can produce polyhydroxyalkanoates from crude glycerol Polyhydroxyalkanoates production from partially purified crude glycerol is presented The yield of polyhydroxyalkanoates achieve at 79 % of dry cell weight under the optimum condition GRAPHICAL ABSTRACT